Seasonal Variations in Seminal Plasma Proteins of Buffalo. Issue 3 (6th March 2014) - Sharma, L; Pandey, V; Nigam, R; Singh, P; Saxena, A; Swain, DK
Contents The study was designed to evaluate the influence of season on semen characteristics and seminal plasma protein profile of buffalo bull semen. Thirty‐six ejaculates were collected in three seasons (winter, summer and rainy) from six adult Bhadawari bulls, and semen characteristics were evaluated immediately after collection. The seminal plasma was harvested by centrifugation and protein profiling, and percentage protein fractions were analysed by SDS‐PAGE. The significant effect of season was observed on ejaculate volume, sperm concentration, progressive motility, percentage live spermatozoa, hypo‐osmotic swelling test (HOST) and acrosomal integrity. The electrophoretogram of seminal plasma proteins revealed 20 protein bands in winter, 23 bands in rainy and 25 bands in summer seasons, illustrating the significant effect of seasons on seminal plasma proteins. Among these protein bands, 18 bands were observed common in semen samples of all three seasons while protein bands of 46, 55, 58, 144 and 160 kDa were found in rainy and summer seasons. The protein bands of 48 and 60 kDa were observed only in winter season, whereas 184 and 200 kDa were reported in summer season only. The protein fractions (protein%) of common protein bands observed in three seasons revealed a significant effect of season on protein bands of 24.5, 66, 70, 72, 84 and 86 kDa. From the study, it was pertinent that bull seminal plasma contains specific proteins in particular season, which may be associated with some of the semen characteristics, and these proteins could be used as markers of the semen quality of buffalo bulls.